(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
Systematic approaches on the material selection for rickshaw frames were applied by cost per unit and weighted property method using modified digital logic. Ashby’s material selection charts were used for preliminary material selection and relative cost analysis. Physical and mechanical properties and the main failure parameters were identified in the frames. Fatigue, associated with corrosion and impact load were identified as the causes of failure for the rickshaw frames. Stress analysis on the frame system was done and for the preliminary selection of materials, the constraints were identified through mathematical models. Magnesium alloy, Titanium alloy, Steel, Aluminum alloy, CFRP, KFRP and GFRP came out from the initial selection. Among the preliminary selected materials, CFRP attained the highest performance index. However, commonly used steel was found to be the optimum for rickshaw frames in terms of figure of merit followed by aluminum alloy and KFRP. Key words: Material selection; Rickshaw frame; Weighted property; Digital logic; Failure analysis DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9584 BJSIR 2011; 46(4): 415-424